Single Live Cell Imaging: Simulation Assisted Nanoscale Imaging of Single Live Cells with Scanning Electrochemical Microscopy (Adv. Theory Simul. 2/2019). Issue 2 (4th February 2019) - Filice, Fraser P.; Li, Michelle S. M.; Ding, Zhifeng
Abstract : Nanoscale imaging of a single live cell by scanning electrochemical microscopy (SECM) is realized by Zhifeng Ding and co‐workers in article number1800124 by simply scanning a nanometer electrode across the surface of the cell. The resulting faradaic current is simulated with a 3‐dimensional model. Cell surface topography, electrode‐to‐cell distance, and cell membrane can be quantified by fitting the experimental results, as is illustrated by the cross‐section curve shown on the cover.